Asuhan Kebidanan Komprehensif dan Berkesinambungan (Continuity of Care) pada Ny. E Usia 29 Tahun di Puskesmas Waimangura, Sumba Barat Daya, Nusa Tenggara Timur - Imelda Jumita Seingo; Heni Hirawati Pranoto (Universitas Ngudi Waluyo, 2024)
The world health organization, World Health Organization (WHO) estimates that 800 women die every day due to complications from pregnancy and the birth process. About 99% of all maternal deaths occur in developing countries. One of the efforts made to reduce MMR and IMR is to provide care to pregnant women and women giving birth carefully and appropriately. This research aims to improve sustainable services for pregnant, maternity, postpartum, BBL and family planning women with standards of care by documenting using SOAP. The author was able to carry out Pregnancy Care from 12/06/23 until the end of the postpartum period on 22/01/24. There were 6 Anatenatal Care examinations using the 10T standard, during the ANC visit, based on the results of the objective data assessment, overall there were no problems. The care provided by the author includes providing vitamin C supplement therapy, folaxin, Fe tablets, as well as IEC regarding adequate rest patterns and fulfilling nutritional/nutritional needs. The patient came on 11/01/2024 at 13.00 WIB, gestational age 38+6 weeks with dilation of 8 cm, the membranes had broken, the mother's general condition was moderate. The author immediately carried out normal delivery care according to standard operating procedures (SOP). The baby was born spontaneously without complications on 11/01/2024 at 15.30 WIB. After that, the author provides midwifery care during the postpartum period and BBL. In the period of assistance during the postpartum period, various education is provided to mothers, one of which is regarding family planning. Care at KF1 – KF4 was normal, there were no problems or complaints experienced by the patient. Midwifery care services during pregnancy, childbirth, postpartum and family planning can be implemented according to standards in a comprehensive and sustainable manner (COC). Abstrak Organisasi kesehatan tingkat dunia, World Health Organization (WHO) memperkirakan 800 perempuan meninggal setiap harinya akibat komplikasi kehamilan dan proses kelahiran. Sekitar 99% dari seluruh kematian ibu terjadi di negara berkembang. Salah satu usaha yang dilakukan untuk menurunkan AKI dan AKB adalah memberi pelayanan pada ibu hamil dan ibu bersalin secara cermat dan tepat. Penelitian ini bertujuan meningkatkan pelayanan yang berkesinambungan pada ibu hamil, bersalin, nifas, BBL, dan KB dengan standar asuhan dengan pendokumentasian menggunakan SOAP. Penulis dapat melakukan Asuhan Kehamilan pada tanggal 12/06/23 sampai dengan berakhir masa nifas tanggal 22/01/24. Pemeriksaan Anatenatal Care sebanyak 6 kali menggunakan standar 10T, dalam masa kunjungan ANC berdasarkan hasil pengkajian data objektif secara keseluruhan tidak ada masalah. Asuhan yang diberikan oleh penulis meliputi pemberian terapi suplemen vitamin C, folaxin, tablet Fe, serta KIE mengenai pola istirahat yang cukup dan pemenuhan gizi/ kebutuhan nutrisi. Pasien datang tanggal 11/01/2024 pukul 13.00 WIB usia kehamilan 38+6 minggu dengan pembukaan 8 cm, ketuban sudah pecah, keadaan umum ibu sedang. Penulis segera melakukan Asuhan Persalinan Normal sesuai standar operasional prosedur (SOP). Bayi lahir spontan tanpa komplikasi pada tanggal 11/01/2024 pukul 15.30 WIB. Setelah itu, penulis memberikan asuhan kebidanan masa nifas dan BBL. Dalam rentang pendampingan masa nifas diberikan berbagai edukasi kepada ibu, salah satunya mengenai KB. Asuhan pada KF1 – KF4 berlangsung normal, tidak ada masalah ataupun keluhan yang dialami pasien. Pelayanan asuhan kebidanan dalam masa kehamilan, persalinan, nifas dan KB dapat dilaksanakan sesuai standar secara komprehensif dan berkelanjutan (COC).